New Insights on the Role of pentraxin-3 in Allergic Asthma - Koussih, Latifa; Atoui, Samira; Tliba, Omar; Gounni, Abdelilah S. (Frontiers in Allergy, 2021)
Pentraxins are soluble pattern recognition receptors that play a major role in regulating innate immune responses. Through their interaction with complement components, Fcγ receptors, and different microbial moieties, Pentraxins cause an amplification of the inflammatory response. Pentraxin-3 is of particular interest since it was identified as a biomarker for several immune-pathological diseases. In allergic asthma, pentraxin-3 is produced by immune and structural cells and is up-regulated by pro-asthmatic cytokines such as TNFα and IL-1β. Strikingly, some recent experimental evidence demonstrated a protective role of pentraxin-3 in chronic airway inflammatory diseases such as allergic asthma. Indeed, reduced pentraxin-3 levels have been associated with neutrophilic inflammation, Th17 immune response, insensitivity to standard therapeutics and a severe form of the disease. In this review, we will summarize the current knowledge of the role of pentraxin-3 in innate immune response and discuss the protective role of pentraxin-3 in allergic asthma.